Remaining Life Assessment of Replaced Intelligent Electric Meter Fused Health Index with Grey Theory - JING Zhen; WANG Li; YANG Mei; YAN Hong-rui; GUO Liang; WANG Zhe-long; ZHANG Jia-hai (Journal of Harbin University of Science and Technology)
To implement intensive measuring assets and other demands of SGCC, and the principle on maintenance and taking advantage of replaced intelligent electric meter, aremnant life assessment model of replaced intelligent electric meter is built by combining health index and grey theory. Remaining life can be deduced by combining grey theory and health index calculation formula of power equipment from British firm EA. An accelerated life test plan is determined according to expertise, and the proposed method is feasible and practicable by using accelerated life test data of replaced intelligent electric meter.